Land Disputes and Efficacy of Revenue and Civil Courts in Pakistan - Abid, Syed Hammad (Journal of Pakistan Administration, 2021)
Disputes over documentation and possession of property directly impact peaceful existence of societies. Loss of property and possession is deemed as loss of honor and dignity. Social, cultural, and customary peer pressure are major factors that trigger violence. Land has always been considered to a valuable asset and a finite resource. Compromises over land, even when made voluntarily, are considered psychological infringements of fundamental and economic rights. Land disputes exist everywhere. From the global to the local. At the domestic level, factors that play catalytic roles in infusing and promoting land disputes are the same that hamper effectiveness of land administration. These include climate change, food insecurity, unemployment, un-planned urbanization, deforestation, and encroachment of state and private land due to poor enforcement of rights.